PENGARUH UKURAN PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN FOOD AND BEVERAGE YANG LISTING DI BURSA EFEK INDONESIA (BEI) - Oktari, Vivi Kumala; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the effect of firm size and corporate governance on earnings management in food and beverage companies listed on the Indonesia Stock Exchange (IDX). The ratio of firm size used as an independent variable is the natural logarithm of total asset (ln total asset). Corporate governance ratios used as independent variables are managerial ownership, proportion of independent board of commissioner and audit committee. While the earning management ratio used as the dependent variable is discretionary accrual. The method used to observe the effect of corporate size and corporate governance on earnings management using multiple linear regression.The data used in this research are secondary data, financial report and annual report annual report. The data listed on the Indonesia Stock Exchange (IDX) for 5 years from 2011-2015 period. Sampling is done by purposive sampling, which is used is 6 companies. Data analysis using multiple linear analysis, t test, f test and coefficient of determination test. The data analysis used multiple linear regression analysis with SPSS 21.The results of this study indicate that the variable firm size partially (t test) has no effect the earnings management, while the variable corporate governance effect on earnings management in food and beverage companies listed on the Indonesia Stock Exchange. Simultaneous test results (F) show the effect on the firm size and corporate governance on earnings management on food and beverages companies listed on the Indonesia Stock Exchange.Keywords: firm size, corporate governance and earning management